Increasing Reproductive Health Knowledge of Indonesian Female Migrant Workers Through Case Study Learning Method - Winarso, Hudi; I'tishom, Reny; Hanna Tabita Hasianna Silitonga (Universitas Airlangga, 2024)
Background: Reproduction health in migrant workers is complicated and difficult to handle. Health education is one of the methods to increase the knowledge about health reproduction. Aims: The study aimed to analyze the knowledge of migrant workers related to reproductive health through case study learning method. Methods: The study is an intervention research. Total respondents were 135 participants. The intervention was conducted in 3 groups of female migrant workers. The intervention given was related to reproductive health with 4 meetings in the first group, 8 meetings in the second group and 12 meetings in the third group. Group 2 and 3 used case study as learning method. The measurement of knowledge of the three groups was through pre-test and post-test. The statistical test used ANOVA to determine differences between intervention groups and T Test to determine the difference between pre-test and post-test scores. Results: There were significant differences in pre-test and post-test scores in all groups and there was significant difference in post-test scores in groups 1 and 3 of p=0.001. Conclusion: Health education given to migrant workers is proven to be able to increase the level of knowledge related to reproductive health. The group that received case study as learning method and more number of meeting, had a better level of knowledge.